2005
DOI: 10.1093/humrep/deh799
|View full text |Cite
|
Sign up to set email alerts
|

Search for mutations involved in human globozoospermia*

Abstract: No mutation was identified among these six patients. Further work is needed, with a larger patient data set, to identify putative genes involved in this form of male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Although these pathophysiologies of sperm motility and morphology are heterogenous, the genetic diagnosis is based on the clinical and laboratory examination, and the appropriate genetic tests (see the section 3.13). In a recent study, no mutation was found among six patients with globozoospermia [30]. Counseling is of paramount importance to inform the couples about the risk of transmitting these disorders to their offspring.…”
Section: Kartagener Syndrome and Other Monomorphic Anomalies Of Spermmentioning
confidence: 98%
See 1 more Smart Citation
“…Although these pathophysiologies of sperm motility and morphology are heterogenous, the genetic diagnosis is based on the clinical and laboratory examination, and the appropriate genetic tests (see the section 3.13). In a recent study, no mutation was found among six patients with globozoospermia [30]. Counseling is of paramount importance to inform the couples about the risk of transmitting these disorders to their offspring.…”
Section: Kartagener Syndrome and Other Monomorphic Anomalies Of Spermmentioning
confidence: 98%
“…Thus, monomorphic anomalies of spermatozoa represent a defined entity with distinct genetic background and variable characteristics as, for example, globozoospermia [13,24] (see the section 3.13). Globozoospermia is found in less than 0.1% of infertile male partners [30]. Although these pathophysiologies of sperm motility and morphology are heterogenous, the genetic diagnosis is based on the clinical and laboratory examination, and the appropriate genetic tests (see the section 3.13).…”
Section: Kartagener Syndrome and Other Monomorphic Anomalies Of Spermmentioning
confidence: 99%
“…No mutations have been found in globozoospermic patients in genes such as Hrb, GOPC and Csnk2a2 that are known to be associated with globozoospermic-phenotypes in mutant mice (Pirrello et al, 2005;Christensen et al, 2006). GOPC 2/2 mice that share most of the characteristics of the human phenotype have confirmed the main role played by the peri-nuclear matrix for acrosome formation and oocyte activation (Yao et al, 2002;Ito et al, 2004Ito et al, , 2009Ito et al, , 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Plusieurs équipes ont séquencé, chez quelques patients atteints, différents gènes comme Csnk2a2 et Csnk2b [15], Hrb, GOPC et Csnk2a2 [16]. Si initialement aucune mutation n'a été retrouvée, mis à part quelques polymorphismes génétiques, une étude récente, analysant les gènes GOPC, HRB, CSNK2a2 et PICK1, a caractérisé une mutation pour ce dernier gène [17].…”
Section: Abstract Globozoocephalia · Genetics · Globozoospermiaunclassified